PEMILIHAN BAHAN SUDU UNTUK PERANCANGAN DAN PEMBUATAN PROTOTIPE TURBIN ANGIN SUMBU HORIZONTAL - M. Yonggi Puriza; Melda Latief (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2018)
Electrical power is a a vital requirement for economic development and social development. Beyond the importance of the function of electrical energy for the community, it is very unfortunate that not all areas in Indonesia that are irrigated plants. The breakdown of power supplies is not separated from the problem of insufficient power generation of electricity. Overcome this problem it is necessary to glance alternative electric energy generation business-friendly environment, available all day long and easily in installation. Wind energy power plants may be a solution. Degan wind speeds in the range 5 m / s in Indonesia need to designed a wind turbine to rotating and generate energy even for a rotating with a low speed. The selected wind turbine is the horizontal axis wind turbine blades having a shapes similar to a propeller - blades aircraft in general. Material planned for the horizontal axis wind the turbine was originally wood that is readily available material and easy to shape. This wooden blade length of about 0.75 m, but after completed and assembled the turbine was not rotate even though the wind speed has reached 4 m / s, this is certainly not fit for purpose of the study. The next material is arkrilik, this type has advantages compared to wood material that is lightweight, thin and of sufficient strength. Expected to advantages, this wind the turbine will be able to work as expected